Idiopathic Chylopericardium: A case Report and Breif Review of Literature - Haraka, Majda; Mourid, Monia El; Boutaleb, Amine Mamoun; Khay, Khadija; Azzouzi, Leila; Habbal, Rachida (International Journal of Cardiovascular Practice, 2019)
Chylopericardium is the accumulation of chylous fluid in the pericardial space. Many etiologies can be found and the treatment depends on the etiology and remains unclear. This rare entity needs some tests to determine its causes. Diagnosis is based on many tools; the pericardial biopsy puncture and lymphoscintigraphy are the most important ones. The treatment requires low fat diet, lipid lowering therapy and surgery in some cases. We here report the first case in the IBN ROCHD university hospital?s Cardiology department of Casablanca, Morocco. It deals with a 32-year-old patient who consulted for dyspnea exacerbation for 18 months, becoming at rest. Chest X-ray and echocardiography were performed discovering pericardial effusion. Pericardiocentesis was performed to confirm the nature of liquid and lymphoscintigraphy showed no abnormal communication between the thoracic duct and pericardium.